Type 2 Diabetes Among People With Posttraumatic Stress Disorder: Systematic Review and Meta-Analysis - Vancampfort, Davy; Rosenbaum, Simon; Ward, Philip B.; Steel, Zachary; Lederman, Oscar; Lamwaka, Alice Veronica; Richards, Justin W.; Stubbs, Brendon (Psychosomatic Medicine, 2016)
To clarify the prevalence and predictors of Type 2 diabetes mellitus (T2DM) in people with posttraumatic stress disorder (PTSD) and where possible compare this to healthy controls.We searched major electronic databases until May 2015 for studies reporting T2DM prevalence in people with PTSD. Two independent authors extracted data and completed methodological quality appraisal. A random-effects meta-analysis was used.From 1171 candidate publications after exclusions, nine publications were included (n = 23,396; 28.6% male; mean age = 35–60 years). The overall prevalence of T2DM was 10.0% (95% confidence interval [CI] = 8.1%–12.0%). Subgroup analysis demonstrated that war veterans experience higher prevalence of T2DM (16.3%; 95% CI = 5.2%–31.8%; n studies = 3, n = 473) compared with mixed samples (11.8%; 95% CI = 6.34–18.7, p < .001; n studies = 4, n = 2753). Increasing age (β = 0.0593, 95% CI = 0.010–0.109, z = 2.34, p = .019), median year of publication (β = −0.08, 95% CI = −0.14 to −0.03, z = −3.09, p = .002), and a lower percentage of white participants (β = −3.21, 95% CI = −5.12 to −1.29, z = −2.28, p = .001) predicted prevalence of T2DM. A relative risk meta-analysis comparing controls (n = 125,723) against those with PTSD (n = 23,203) demonstrated a significantly increased risk of T2DM (n studies = 5, relative risk = 1.49, 95% CI = 1.17–1.89, p = .001).People with PTSD are at a high risk for developing T2DM. The current findings should, however, be interpreted with caution because most studies were based on self-report data.
Keywords: diabetes mellitus, glucose, PTSD.